Analisa Kebutuhan Kapasitas Kapasitor Bank Untuk Menjaga Pasokan Tegangan Operasi Pada Bus Pompa Motor HCT Duri - Ayyubi, Farisi Al; Sukma, Dian Yayan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
PT. Chevron is one of the largest oil companies in the world. To be able to do maximum production, PT. Chveron need to make sure all goes well with the production facilities. One of the important production facilities is the delivery pumping motor. Duri operation area has 7 pumping motors to be installed with capacity of 550HP each of them. Each of individual pumping motor requires 4,16 kV which supplied by 13,8 kV of distribution network Prior to the installation, it is necessary to have a study to anticipate drop voltage or overvoltage case. This paper proposes capacitor banks installation approach. The approach uses several trial errors in the placement of capacitor in the respective bus within distribution network. The ETAP simulation result shows 4 buses with following configuration i.e bus 1 and bus 2 with 600 kVar, in the other case bus 3 and bus 4 with 300 kVar.Keywords:Voltage drop, feeder distribution network,13,8 kV and 4,16 kV network, capacitor bank